The tuna industry in General Santos City value chain and net margins analysis - Kho, Jewel Lyn V.
The tuna industry in General Santos City has contributed in the economy of the Philippines with tuna being its third top export products. The industry has generated thousands of jobs in the country. However, with the decline in the production of tuna as a result of natural factors, regulating policies, and increasing cost of inputs to fishing, there is a need for appropriate intervention to benefit those who are affected by the existing problems and issues. The study utilized both value chain analysis to map the chain and plot the influence of its enabling environment and support services, and net margins analysis to examine the benefit distribution among chain actors. The value chain analysis identified six major and at times overlapping processes: (1) financing, (2) fishing, (3) trading, (4) distribution (whole tuna export, and local distribution), (5) processing and canning, and (6) consumption. Moreover, the analysis showed the enabling environment and different support services in the industry contributed to its growth. However there are still occurring issues that needs immediate solution. The Net Margins analysis includes the computation and comparison of the high catch event, low catch event, and average catch event margins of the respondents. The analysis revealed that the fishers, most of the time, are price takers but earns the highest net margin in terms of kilograms produced and sold among the actors interviewed. A "laras" scheme of selling was also found emerging that contributes to more competition among actors of tuna trading. Furthermore, the study verified that high fuel price is the most significant cost in tuna production.